Effectiveness of Group Work Strategy on the Achievement of EFL Secondary School Students in Ma’rib City - Al-Maghashah, Mohammed Zabnallah Mobarak; Almuslimi , Fazee Khalid Alezi Mohammed (International Journal of Linguistics and Translation Studies, 2023)
The aim of this study is to determine the effectiveness of group work strategy on the achievement of secondary school students in Ma’rib City. To achieve the objectives of the study, the research was organized according to a quasi-experimental design with experimental and control groups. The experimental (n=30) and the control group (n=30) were purposefully chosen to participate in the experiment among the 10th grade students in Al-Methaq secondary school in Ma’rib City in the first semester of the study year (2021-2021). The study instrument was an achievement test administered before and after conducting the experiment. The validity and reliability of the instrument were ensured. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS). The obtained data were calculated and tabulated for analysis using descriptive statistics (means, standard deviation, and rank mean). The results of the study showed a positive effect of using group work strategy on students’ achievement in English. In addition, the results showed that there were statistically significant differences in the mean scores between the two groups in the achievement of English. The researcher attributed this result to the use of group work strategy. In conclusion, the study recommends the need to implement active learning strategies in teaching and learning English to ensure better outcomes for students.